α-Fe2O3 material for reducing and repairing PFASs pollution in water bodies and its preparation method and application
By hydrophobic and pore modification on the α-Fe2O3 material, an α-Fe2O3 nanoparticle layer with a hydrophobic pore structure is formed, and PFASs is reduced and degraded, which solves the problem of difficult degradation of PFASs pollution in the prior art, and achieves efficient PFASs degradation and defluorination effects.
Patent Information
- Application Number
- CN202311685058.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-08
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-12-08
AI Technical Summary
The prior art is difficult to effectively degrade and contaminate PFASs in defluorinated water bodies, especially the degradation effect of advanced oxidation systems on PFASs and their alternatives is limited.
By hydrophobic and pore modification on the α-Fe2O3 material, an α-Fe2O3 nanoparticle layer with a hydrophobic domain pore structure is formed. It is used as a catalyst, combined with sulfite as a hydrated electron source substance and ultraviolet light as a driving light source, and PFASs are reduced and degraded.
It improves the adsorption capacity and degradation efficiency of PFASs, weakens the interference of dissolved oxygen and hydrogen ions, broadens the treatment conditions, and significantly improves the harmlessness of PFASs defluorination in water bodies.
Smart Images

Figure CN117920217B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of water environment pollution control, and specifically relates to an α-Fe 2 O 3 Materials, preparation methods and applications thereof. Background Art
[0002] Per-polyfluoroalkyl substances (PFASs) are widely used in water-based fire-fighting foams, waterproof fabrics and daily life equipment due to their excellent chemical, thermal and biological stability. In 2018, the global production of perfluoropolymers exceeded 230,000 tons, and more than 9,000 types of PFAS were produced. It is estimated that by 2030, the total cumulative emissions of perfluoroalkanoic acids will exceed 46,000 tons worldwide. The extremely stable CF bond has enabled PFASs to be detected on a global scale, with concentrations as high as thousands of nanograms per liter. With the discovery of the biological toxicity and enrichment of PFASs, PFOA (perfluorooctanoic acid) and PFOS (perfluorooctane sulfonic acid) have been clearly included in the Stockholm Convention's blacklist of alternative bans. The U.S. Environmental Protection Agency has jointly established a drinking water recommended value of 70 ng / L for PFOA and PFOS.
[0003] With the banning of traditional PFAS, a series of substitutes have emerged and invaded the global water environment in a short period of time, such as GenX, a substitute for PFOA. GenX is a short-chain perfluoroalkyl chemical, and its chemical name is hexafluoropropylene oxide dimer acid (HFPO-DA for short). What is more worrying is that the degradation degree of PFASs and their substitutes by advanced oxidation systems such as Fenton and sulfate is limited, and the defluorination mineralization effect is even more negligible, which cannot meet the actual PFASs contaminated water treatment and purification.
[0004] In contrast, advanced reduction technology using hydrated electrons as active species has shown good degradation and defluorination effects on PFASs. Commonly used hydrated electron source substances (i.e., reducing agents) mainly include sulfites, iodides, and indoles. However, there are some problems with advanced reduction remediation technology based on hydrated electrons: (1) Non-targeted consumption of reducing agents, that is, highly reducing hydrated electrons are easily consumed by dissolved oxygen, hydrogen ions, natural organic matter, or other reactive substances in the water environment, resulting in low efficiency of reducing agents; (2) The interaction between reducing agents and target pollutants is poor, and the reaction distance is far, which reduces the reaction rate and endpoint degree. How to improve the utilization rate of hydrated electrons has become one of the main trends in current research.
[0005] The development of efficient and stable repair catalytic materials is the core of water chemical remediation technology. In this field, we look forward to developing more types of catalyst materials to achieve efficient remediation of PFASs pollution in water. Iron-based materials themselves have low toxicity, strong biocompatibility and strong modifiability. After a lot of exploration, the present invention has found that in the treatment of α-type ferric oxide (α-Fe 2 O 3 ) after hydrophobic and pore modification, it has a stronger hydrophobic force on the target pollutant PFASs, shortens the attack distance of hydrated electrons on PFASs, and improves the reaction efficiency; and can limit some PFASs and hydrated electrons to the α-Fe 2 O 3 The voids in the material resist interference from dissolved oxygen and hydrogen ions, broaden the practical treatment conditions for PFAS, and increase the scope of application of hydrated electrons for the degradation and defluorination of PFASs. Summary of the invention
[0006] A brief overview of the disclosure is given below in order to provide a basic understanding of certain aspects of the disclosure. It should be understood that this overview is not an exhaustive overview of the disclosure. It is not intended to identify key or important parts of the disclosure, nor is it intended to limit the scope of the disclosure. Its purpose is simply to give certain concepts in a simplified form as a prelude to a more detailed description discussed later.
[0007] In order to solve the above technical problems, the technical solution provided by the present disclosure is:
[0008] The present invention provides a first aspect of an α-Fe ion-containing polymer for reducing and repairing PFAS pollution in water bodies. 2 O 3 A method for preparing a material, comprising:
[0009] Precursor preparation steps: dissolving a trivalent iron source to obtain an iron salt solution, adding a dispersant under stirring conditions to coat and separate the iron ions to generate a flocculent brown precipitate to obtain a precursor suspension, separating the precipitate and washing, purifying, drying, crushing and sieving it in sequence to obtain a precursor;
[0010] Calcination step: heat-treating the precursor in an inert atmosphere, and then crushing and sieving to obtain the α-Fe 2 O 3 The material is red and has a hydrophobic confined pore structure. 2 O 3 Nanoparticle layer.
[0011] In the above preparation method, as a preferred embodiment, in the precursor preparation step, the dispersant is oleylamine or hexadecyltrimethylammonium bromide (CTAB for short), which has the function of coating and separating the iron ions, which is beneficial to the control of the morphology of the iron oxide nanoparticles during the subsequent heat treatment process, avoiding excessive agglomeration and maintaining effective contact between the particles.
[0012] In the above preparation method, the α-Fe 2 O 3 The precursor is calcined in a nitrogen atmosphere or an inert gas atmosphere, which allows the precursor to be orderly condensed to form a multilayer nanoparticle structure with a hydrophobic surface and micro-nano confined pores. Since PFAS has a hydrophobic tail, it is easy to combine with the material by hydrophobic effect; the reduction effect of PFAS is easily inhibited by dissolved oxygen and hydrogen ions, while the confined pores can resist the interference of some dissolved oxygen and hydrogen ions. Therefore, the α-Fe 2 O 3 The material can enhance the adsorption of hydrophobic target pollutants PFASs and provide a confined reaction space for hydrated electrons to attack PFASs, thereby reducing the effects of dissolved oxygen or hydrogen ions on degradation and defluorination performance in the actual environment.
[0013] In the above preparation method, as a preferred embodiment, in the precursor preparation step, the washing and purification treatment includes using ethanol / n-hexane with a volume ratio of 1:4 to remove oleylamine and inorganic ion impurities that are not combined with Fe; the specific method is exemplified as follows: first, the precursor suspension is centrifuged to discard the supernatant, an appropriate amount of 1:4 ethanol / n-hexane washing solution is added, and the mixture is shaken and washed on an oscillator at 2500r / min for 30 minutes, and vacuum freeze-dried after centrifugation for solid-liquid separation.
[0014] In the above preparation method, as a preferred embodiment, in the precursor preparation step, the trivalent iron source is selected from ferric nitrate, ferric nitrate nonahydrate Fe(NO 3 ) 3 9H 2 O, Ferric chloride, Ferric chloride hexahydrate FeCl 3 6H 2 O and at least one of trivalent iron salts such as ferric sulfate.
[0015] In the above preparation method, as a preferred embodiment, in the precursor preparation step, the dispersant is oleylamine, and the ratio of the amount of oleylamine added to the volume of the iron salt solution is 1:10-50 (such as 1 / 15, 1 / 20, 1 / 25, 1 / 30, 1 / 35, 1 / 40, 1 / 45, etc.); by changing the volume ratio of the oleylamine added to the iron salt solution, the amount of oleylamine coated on the precursor powder is changed, thereby affecting the subsequent calcination heat treatment of α-Fe 2 O3 particle size structure and surface properties.
[0016] In the above preparation method, as a preferred embodiment, in the precursor preparation step, after the oleylamine is added dropwise to the stirring iron salt solution, the solution is stirred at a constant speed of 300-1000r / min (such as 400r / min, 500r / min, 600r / min, 700r / min, 800r / min, 900r / min, etc.) for 10-60min (such as 15min, 20min, 30min, 40min, 50min, 55min, etc.).
[0017] In the above preparation method, as a preferred embodiment, in the precursor preparation step, the drying treatment is a vacuum freeze-drying treatment.
[0018] In the above preparation method, as a preferred embodiment, in the calcination step, the target temperature of the heat treatment is 600-1000°C (such as 650°C, 700°C, 800°C, 900°C, 9500°C, etc.), and the treatment time is 3-12h (such as 3.5h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, etc.). The treatment time refers to the constant temperature time after reaching the treatment temperature.
[0019] In the above preparation method, as a preferred embodiment, in the calcination step, the heat treatment includes heating the precursor to 780-820°C (such as 785°C, 790°C, 800°C, 810°C, 815°C) at a heating rate of 5±1°C / min and then anaerobic calcining at a constant temperature for 5-7h. The calcination step can be carried out in a tubular furnace or other heat treatment equipment.
[0020] In the above preparation method, as a preferred embodiment, in the calcination step, the material obtained after the heat treatment is crushed to pass through a 200-mesh sieve.
[0021] The second aspect of the present disclosure provides an α-Fe for reducing and repairing PFASs contamination in water bodies. 2 O 3 The material is prepared by the above method. 2 O 3 The material is a nanoparticle with a size of 91±27nm. The particle size is regular and uniform. The particles are interconnected to form a layered three-dimensional structure. The median pore size is 1.1285nm. 2 O 3 The structural properties of the material are stable after catalytic reduction degradation reaction, and the total amount of iron ion dissolution is less than 0.2 mg / L, which meets the environmental standards for drinking water sources in my country.
[0022] The third aspect of the present disclosure provides an α-Fe for reducing and repairing PFASs pollution in water bodies. 2 O 3 Applications of materials include: 2 O 3 The material is used as a catalyst, sulfite is used as a hydrated electron source and reducing agent, and ultraviolet light is used as a driving light source to reduce and degrade PFASs contaminated water. Ultraviolet light can use ultraviolet LEDs, low-pressure mercury lamps, and other light sources that can excite light waves emitted by 254nm bands. The 254nm radiation in natural light is very weak, so it is difficult to degrade PFAS pollution in water under natural light conditions.
[0023] The above-mentioned α-Fe for reducing and repairing PFASs pollution in water 2 O 3 Application of materials, as a preferred embodiment, the sulfite is at least one of sodium sulfite, sodium bisulfite, potassium sulfite, potassium bisulfite, etc.
[0024] The above-mentioned α-Fe for reducing and repairing PFASs pollution in water 2 O 3 Application of the material, as a preferred embodiment, under anaerobic conditions, the α-Fe 2 O 3 The dosage of the material is 0.1-1g / L (such as 0.2g / L, 0.5g / L, 0.8g / L, etc.), the dosage of the sulfite is 1-20mmol / L (such as 2mmol / L, 5mmol / L, 8mmol / L, 10mmol / L, 12mmol / L, 15mmol / L, 18mmol / L, etc.), and the treatment time is 12-48h (such as 15h, 18h, 24h, 30h, 36h, 40h, 45h, etc.). Preferably, the anaerobic condition is a dissolved oxygen content of 0.2±0.1mg / L.
[0025] The above-mentioned α-Fe for reducing and repairing PFASs pollution in water 2 O 3 Application of the material, as a preferred embodiment, under aerobic conditions, the α-Fe 2 O 3 The dosage of the material is 0.1-0.2 g / L, the dosage of the sulfite is 5-20 mmol / L, and the treatment time is 24-48 hours. Preferably, the aerobic condition is a dissolved oxygen content of 8.9±0.1 mg / L.
[0026] Compared with the prior art, the beneficial effects of the present disclosure include but are not limited to:
[0027] 1) The catalyst α-Fe for reducing and repairing PFASs pollution in water provided by the present disclosure2 O 3 Materials, including Fe 2 O 3 The particles have a hydrophobic surface, and two adjacent Fe 2 O 3 There is a confined space between the particles, which is composed of nano-Fe with a specific size (97±21nm). 2 O 3 After the particles are stacked on each other, a special spatial structure is formed. This confined space can limit the movement of reactant molecules and broaden the degradation pathway. Under ultraviolet light excitation, the per-polyfluoroalkyl substances quickly aggregate on the hydrophobic Fe 2 O 3 The particle surface is better degraded within the confined space, thereby promoting the reduction and remediation of per- and polyfluoroalkyl substance pollution in water bodies.
[0028] 2) The preparation method provided in the present disclosure is a simple co-precipitation-heat treatment two-step method to synthesize α-Fe 2 O 3 Nanoparticle layer material, while making α-Fe 2 O 3 It has a hydrophobic surface and confined space (hereinafter referred to as hydrophobic confined α-Fe 2 O 3 ), shortening the time required for material preparation and making the steps simpler. 2 O 3 The material can quickly and efficiently catalyze PFASs and their substitutes such as GenX.
[0029] 3) The water body remediation method provided in the present disclosure adopts the above-mentioned hydrophobic confined α-Fe 2 O 3 Nanoparticle layer materials to enhance UV / SO 3 2- The system catalytically reduces PFASs and establishes an efficient water pollution remediation system; through the analysis of the catalytic degradation performance of simulated PFASs-contaminated water samples, it is found that the above system can achieve the purpose of efficiently remediating PFASs water pollution.
[0030] 4) The novel hydrophobic confined α-Fe 2 O 3 Nanoparticle layer material, which has been proven to enhance the defluorination effect of PFASs in water. The present disclosure can adjust the added material and reducing agent according to the different PFAS contents in the polluted water. 2 O 3The material can increase the concentration of effective hydrated electrons and slow down the consumption of hydrated electrons by dissolved oxygen and hydrogen ions, thereby improving the degree of defluorination and mineralization of PFAS in water bodies and having a high value for water pollution control.
[0031] 5) The present invention discloses a hydrophobic confinement of α-Fe 2 O 3 The nanoparticle layer material was used to repair 10 mg / L GenX simulated polluted water, and the effects of anaerobic system / aerobic system (Aerobic open system), catalyst content and pH on the degradation and mineralization of PFASs were explored, and a repair scheme suitable for aerobic / aerobic system was obtained. 2 O 3 Add UV / sulfite (UV / SO 3 2- ) system, the degradation and defluorination rates of GenX with an initial concentration of 10 mg / L were 99.7% and 88.5%, respectively, which was higher than that of UV / SO 3 2- The control group increased by 7.9% and 17.5% respectively. Under aerobic conditions, UV / SO 3 2- The degradation and defluorination rates of GenX in the control group were only 22.0% and 10.9%, respectively, while when α-Fe 2 O 3 After the introduction, the degradation and defluorination rates of GenX increased to 92.3% and 57.4%, respectively. 2 O 3 The introduction of α-Fe greatly enhanced the degradation and defluorination of GenX. 2 O 3 Nanoparticle layer materials provide the possibility for effective remediation of PFASs pollution in actual water bodies and have important scientific research value and application significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The hydrophobic confined α-Fe prepared in Example 1 2 O 3 Schematic diagram of the characterization of nanoparticle layer materials; (a) and (b) are α-Fe 2 O 3 SEM images magnified 10,000 and 50,000 times; (c) is α-Fe 2 O 3 Transmission electron micrograph of α-Fe 2 O 3High-resolution transmission electron microscopy (HRTEM) image of α-Fe 2 O 3 EDS images, (e1) and (e2) are the distribution diagrams of Fe and O elements, respectively, indicating that Fe and O in α-Fe 2 O 3 Evenly distributed in the middle.
[0033] Figure 2a The α-Fe prepared in Example 1 2 O 3 XRD diffraction pattern.
[0034] Figure 2b The α-Fe prepared in Example 1 2 O 3 O1s element XPS fine spectrum.
[0035] Figure 2c The α-Fe prepared in Example 1 2 O 3 Fe 2p element XPS fine spectrum.
[0036] Figure 2d The α-Fe prepared in Example 1 2 O 3 Electron paramagnetic resonance (EPR) spectra of oxygen vacancies.
[0037] Figure 3a The results show that the UV light blank group, UV / SO 3 2- Control group and UV / SO 3 2- and α-Fe 2 O 3 The catalytic test results of the experimental group on GenX.
[0038] Figure 3b The effect of different doses of α-Fe under anaerobic conditions is shown in the example 2 O 3 Effect on the catalytic degradation performance of GenX.
[0039] Figure 3c The effect of different α-Fe 2 O 3 Effect of materials on the catalytic degradation performance of GenX.
[0040] Figure 4 The effect of different initial pH conditions on the degradation and defluorination of GenX under anaerobic conditions in the effect example is shown.
[0041] Figure 5 The α-Fe prepared in Example 1 2 O 3 Photo of the hydrophilicity and hydrophobicity contact angle test.
[0042] Figure 6 The α-Fe prepared in Example 1 2 O 3 Pore size distribution diagram.
[0043] Figure 7 The in situ DMPO spin-trapping EPR spectra in the effect examples are respectively obtained by using water and methanol as solvent systems.
[0044] Figure 8 α-Fe 2 O 3 After intervention, UV / SO 3 2- (abbreviated as UV / S in the figure) and α-Fe 2 O 3 Schematic diagram of the degradation mechanism of GenX in the system.
[0045] Figures 9a to 9c It is shown that GenX is UV / SO 3 2 - (abbreviated as UV / S in the figure) and α-Fe 2 O 3 Possible and plausible degradation pathways in the system. DETAILED DESCRIPTION
[0046] The following examples are provided to facilitate a better understanding of the present disclosure, but are not intended to limit the present disclosure. The experimental methods in the following examples are all conventional methods unless otherwise specified.
[0047] Unless otherwise specified, other experimental materials used in the following examples were purchased from conventional biochemical reagent stores.
[0048] Example 1
[0049] (a) α-Fe 2 O 3 Preparation of precursor:
[0050] With Fe(NO 3 ) 3 9H 2 O is an iron source dissolved in water (concentration of 93.34 mmol / L), oleylamine with a volume of 1 / 25 of the iron salt solution is added dropwise into the reactor, and stirred at a rate of 600 r / min for 30 min to generate a flocculent brown precipitate. The precipitate is separated, washed and purified with a 1:4 volume ratio of ethanol / n-hexane mixture, vacuum freeze-dried, ground to disperse it, and passed through a 200-mesh sieve to obtain a precursor.
[0051] (II) Hydrophobic confined α-Fe 2 O 3 Synthesis of Nanoparticle Layer Materials:
[0052] The above precursors were weighed and placed in a corundum ark, transferred to a tube furnace, and a nitrogen atmosphere was introduced for 30 min to exhaust the air. The temperature was raised to 800 °C at a heating rate of 5 ± 1 °C in an anaerobic environment and maintained for 6 h. After cooling to room temperature, the precursors were taken out, ground, sieved through a 200-mesh sieve, and stored for later use. 2 O 3 Material.
[0053] (III) Hydrophobic confined α-Fe 2 O 3 The material characterization is as follows:
[0054] The surface morphology of the samples was analyzed using a scanning electron microscope (SEM) (model: SU3500, Japan). The surface morphology of the samples was further analyzed using a transmission electron microscope (TEM) (model: TF20 Jeol 2100F). Before testing, the samples were dispersed in anhydrous ethanol, and the suspension was dripped onto a copper mesh and allowed to air dry naturally. X-ray powder diffraction (X-raydiffraction, abbreviated as XRD) (model: Rigaku Smartlab SE) and X-ray photoelectron spectroscopy (XPS) (model: Thermo Fisher Scientific K-Alpha spectrometer) were used to analyze the α-Fe 2 O 3 The surface structure of the material was analyzed using a contact angle / surface tension meter (Chengde Dingsheng JY-82C video contact angle meter). 2 O 3 The hydrophilicity of the materials was analyzed.
[0055] Figure 1 Hydrophobic confined α-Fe 2 O 3 Schematic diagram of the characterization of nanoparticle layer materials. Figure 1 (a) and (b) are α-Fe 2 O 3 SEM images of the material magnified 10,000 and 50,000 times show that α-Fe 2 O 3 The material is composed of particles with a size of 91±27nm, which are interconnected to form a layered three-dimensional structure, and the main pore size distribution is 1.1285nm (reference Figure 6 ), which provides sufficient confined space for the degradation reaction of GenX. Figure 1 (c) is α-Fe 2 O 3 Transmission electron microscope (TEM) photos of the material show a rich void structure. Figure 6 The pore distribution in Figure 1 To. Figure 1 (d) is α-Fe 2 O 3 The high-resolution transmission electron microscopy (HRTEM) image of the material shows that the main exposed crystal plane is {110} and the lattice spacing is 0.26nm, which is consistent with the {110} crystal plane in the XRD spectrum in Figure 2. Figure 1 (e) is α-Fe 2 O 3 EDS images of the material, (e1) and (e2) are the distribution diagrams of Fe and O elements, respectively, indicating that Fe and O in α-Fe 2 O 3 The EDS image further shows that α-Fe 2 O 3 The above characterizations show that the synthesis rate is high and the distribution is uniform. Figure 2d EPR signal g = 2.003) of α-Fe 2 O 3 The successful preparation of nanoparticles (layers), where particles refer to single iron oxide particles and layers refer to the orderly stacking of particles to form a layer structure.
[0056] Figure 2a α-Fe 2 O 3 The XRD diffraction pattern of the material, the diffraction peaks at 24.1°, 33.1°, 35.6°, 40.8°, 49.4°, 54.1°, 57.6°, 62.5°, 71.9°, 63.9°, 75.3° in the XRD pattern are consistent with the α-Fe 2 O 3 (JCPDS 33-0664) correspond to the same, corresponding to nano α-Fe 2 O 3 The crystal planes of the particles are {012}, {104}, {110}, {113}, {024}, {116}, {018}, {214}, {300}, {1010} and {220}, among which the {110} characteristic crystal plane is Figure 1 The HRTEM in (d) is consistent with that in Figure 1. Figure 2a The upper right corner is α-Fe 2 O 3 The XPS full scan spectrum of the material, in which the Fe and O element peaks further prove the α-Fe 2 O 3 The material was successfully prepared. Figure 2b α-Fe 2 O 3The O1s XPS fine spectrum of the material shows three peaks at binding energies of 529.9 eV, 531.6 eV and 532.8 eV, corresponding to lattice oxygen, oxygen vacancies and surface adsorbed oxygen, respectively. The proportion of oxygen vacancies is 31.4%, indicating the presence of a large number of oxygen vacancies. Figure 2c α-Fe 2 O 3 The XPS fine spectrum of the Fe element of the material shows characteristic peaks at binding energies of 711.1 eV and 724.8 eV, corresponding to Fe 2P3 / 2 and Fe 2P1 / 2, respectively, corresponding to trivalent iron, in addition to satellite peaks. Figure 2d α-Fe 2 O 3 The electron paramagnetic resonance spectroscopy (EPR) oxygen vacancy signal of the material was used to further verify the α-Fe 2 O 3 The presence of oxygen vacancies in the material, the strong EPR signal of oxygen vacancies is shown at g = 2.003. The formation of oxygen vacancies is mainly attributed to the 800 ° C treatment under oxygen-free conditions. Oxygen vacancies can attract electrons, promote the adsorption of reaction substrates on the catalyst surface and form a narrow band gap to enhance light utilization.
[0057] Figure 5 α-Fe 2 O 3 From the test photo of the hydrophilicity and hydrophobicity contact angle of the material, it can be seen that its contact angle is 125.16°, >90°, which is a hydrophobic surface and can significantly reduce the surface tension of the target solution.
[0058] Figure 6 α-Fe 2 O 3 The pore size distribution of the material, the median pore size is 1.1285nm, indicating that α-Fe 2 O 3 The material has micro-nano confined pores and can become a confined space.
[0059] Comparative Example 1
[0060] The only difference between this comparative example and Example 1 is that the calcination is carried out in an air atmosphere, the calcination temperature is 400° C., and the other steps and process conditions are the same.
[0061] Effect Example
[0062] (IV) Hydrophobic confined α-Fe 2 O 3 Materials catalytic reduction and degradation of PFASs in water:
[0063] In this example, GenX was used as the water pollutant to prepare simulated wastewater, and the α-Fe 2 O 3The material was used as a catalyst, and the following catalytic reduction degradation experiment was carried out.
[0064] (1) Effect of dissolved oxygen content in the reaction system on GenX removal rate and defluorination rate: Two reaction systems, an anaerobic system and an aerobic system, were set up. In the anaerobic system, the dissolved oxygen content was 0.2±0.1 mg / L, the catalyst dosage was 0.3 g / L, the pollutant GenX concentration was 10 mg / L, and the reducing agent NaHSO 3 The concentration was 20mmol / L (sometimes abbreviated as mM) and the reaction time was 48h. Figure 3a .
[0065] The dissolved oxygen content in the aerobic system was 8.9 ± 0.1 mg / L, the catalyst dosage was 0.1 g / L, the pollutant GenX concentration was 10 mg / L, and the reducing agent NaHSO 3 The concentration was 20 mM and the reaction time was 48 h. Figure 3c .
[0066] (2) Hydrophobic confined α-Fe 2 O 3 Effect of material dosage on GenX removal rate and defluorination rate: Under anaerobic conditions (dissolved oxygen content of 0.2±0.1 mg / L), the catalyst dosage was set to 0.1 g / L, 0.3 g / L, and 0.5 g / L, respectively. The pollutant GenX concentration was 10 mg / L, and the reducing agent NaHSO 3 The concentration was 20 mM and the reaction time was 48 h. Figure 3b .
[0067] (3) Effect of reaction system pH on GenX removal rate and defluorination rate: In order to further verify the hydrophobic confined α-Fe 2 O 3 The material's anti-interference ability to hydrogen ions was tested at different pH values of 4, 8, and 12, respectively, under anaerobic conditions (dissolved oxygen content of 0.2 ± 0.1 mg / L), with a catalyst dosage of 0.3 g / L, a pollutant GenX concentration of 10 mg / L, and a reducing agent of NaHSO 3 The concentration was 20 mM and the reaction time was 48 h. Figure 4 For the experimental group with an initial pH of 12, the total amount of iron in the solution after the reaction was measured by o-phenanthroline spectrophotometry was less than 0.2 mg / L, indicating that α-Fe 2 O 3 The structural properties of the material are stable after catalytic reduction degradation reaction, and the total amount of iron ion dissolution is less than 0.2 mg / L, which meets the environmental standards for drinking water sources in my country.
[0068] (4) Using DMPO free radical scavenger, in situ EPR spectroscopy experiments were performed with water and methanol as solvents to capture the free radical signals generated in the system. 3 - The initial concentrations of α-Fe prepared in Example 1 were 100 mM and 20 mM, respectively. 2 O 3 , denoted as Fe(800), the concentrations were 0.1 g / L and 0.3 g / L respectively, and the initial pH of the solution was adjusted to 12±0.1. A 254 nm ultraviolet lamp was used as the light source, and the EPR spectra were recorded after irradiating all samples for 3 minutes. The results are shown in Figure 7 .
[0069] (V) Hydrophobic confined α-Fe 2 O 3 Material Strengthening UV / SO 3 2- Mechanistic study of the defluorination of GenX by the system:
[0070] To explore the α-Fe 2 O 3 Material Strengthening UV / SO 3 2 - The defluorination mechanism of GenX was investigated by using contact angle / surface tension meter, specific surface area and pore volume analyzer to analyze the α-Fe 2 O 3 The surface properties and pore structure of the material were analyzed and the results showed that α-Fe 2 O 3 The material surface is hydrophobic and has micro-nano confined pores, which enhances the reaction efficiency between hydrated electrons and the target GenX.
[0071] Furthermore, the in situ electron paramagnetic resonance results showed that α-Fe 2 O 3 After the introduction of the material, the concentration of hydrated electrons in the reaction system increased significantly. 2 O 3 The introduction of the material strengthens the interaction between sulfite and GenX, reduces the attack distance of hydrated electrons on GenX, resists the interference of some dissolved oxygen, and maintains a higher concentration of effective hydrated electrons in the system. 2 O 3 The hydrophobic surface of the material attracts GenX and hydrated electron source materials (such as sodium bisulfite), and the confined space resists dissolved oxygen and hydrogen ions, thereby improving the degree of degradation and defluorination.
[0072] (VI) Experimental results
[0073] 1. Hydrophobic confined α-Fe 2 O 3 Material Strengthening UV / SO 3 2- Defluorination of GenX
[0074] To verify the α-Fe 2 O 3 Material Strengthening UV / SO 3 2-system for the defluorination of GenX. GenX was selected as the representative target pollutant, and the content of the target pollutant was determined by liquid chromatography-high-resolution mass spectrometry (LC-HRMS) technology. The initial pH of the system, anaerobic / aerobic conditions, catalyst dosage, and reducing agent NaHSO were also investigated. 3 Effect of dosage on GenX degradation and defluorination. For experimental conditions, see Part (IV) above.
[0075] Figure 3a The UV light blank group, UV / SO 3 2- Control group and UV / SO 3 2- +α-Fe 2 O 3 The catalytic test results of each experimental group on GenX. Initial conditions of the experiment: [GenX] 0 =10mg / L; HSO 3 - =20mM; T = 25°C; α-Fe 2 O 3 Dosage = 0.3 g / L. It can be seen that under anaerobic conditions, the degradation rate and defluorination rate of GenX can reach 99.7% and 88.5% respectively.
[0076] In this application Figure 3a to Figure 3c , Figure 4 The solid lines represent the degradation of GenX, and the dashed lines represent the defluorination. Figure 3b It shows that under anaerobic conditions, different α-Fe 2 O 3 The effect of UV / S+Fe system on GenX degradation and defluorination at different concentrations. It was finally determined that the most efficient catalyst dosage under anaerobic conditions was 0.3 g / L.
[0077] Figure 3c The results show that the α-Fe obtained in Example 1 and Comparative Example 1 were applied under aerobic conditions. 2 O 3 Catalyst, in α-Fe 2 O 3 The effect of UV / S+Fe on the degradation and defluorination of GenX at a concentration of 0.1 g / L. It shows that under the initial reaction conditions (pollutant GenX concentration of 10 mg / L, reducing agent NaHSO 3 The concentration was 20 mM, pH = 12, and the reaction time was 48 h. Under aerobic conditions, the α-Fe prepared in Example 1 was applied by UV / S system. 2 O3 The degradation rate and defluorination rate of GenX by the catalyst can reach 92.3% and 57.4% respectively, which is much higher than that of the control group, and the reaction end point can be advanced from 48h to 24h. 2 O 3 Nanoparticle layer materials can effectively remove PFASs pollution in water.
[0078] Figure 4 The effect of different initial pH conditions on GenX degradation (solid line) and defluorination (dashed line) under anaerobic conditions is shown. The initial conditions ([GenX] 0 =10mg / L; HSO 3 - =20mM; T = 25°C). As can be seen from the figure, when the initial pH value of the reaction drops from 12 to 8, there is still a strong degradation and defluorination effect on GenX. If the GenX concentration of 10mg / L in this experimental condition is further reduced, a higher treatment effect will be achieved, which will meet the treatment requirements of actual environmental water samples with low PFAS concentrations.
[0079] from Figure 7 The EPR spectrum shown in FIG. 2 O 3 Add to UV / SO 3 2- After the system was established, the signal peak of hydrated electrons was significantly enhanced, no matter under anaerobic or aerobic conditions.
[0080] 2. α-Fe 2 O 3 Mechanism of material catalytic reduction of PFASs
[0081] In order to clearly explain the 2 O 3 After intervention, UV / SO 3 2- and α-Fe 2 O 3 The degradation mechanism of GenX in the system is shown in Figure 2. A brief schematic diagram of the degradation mechanism is drawn. Figure 8 There are three main steps: Ⅰ) Attraction and diffusion of GenX and sulfite on the surface of the material; Ⅱ) Degradation in confined pores under UV excitation; Ⅲ) Differential degradation under anaerobic / aerobic conditions.
[0082] 3. Hydrophobic confined α-Fe 2 O 3 Analysis of the degradation pathway of GenX by material-enhanced catalysis
[0083] The intermediates generated during the degradation of GenX were determined by LC-HRMS, and combined with the theoretical calculation results of the surface active sites of GenX molecules, the degradation pathway of GenX under anaerobic conditions was proposed. Figure 9a-9cIt is shown that GenX can be synthesized under anaerobic conditions under UV / S+α-Fe 2 O 3 Possible and reasonable degradation pathways in the system. Among them, Figure 9a This is the molecular structure model of GenX. Figure 9b Isosurfaces of the Fukui function f- for electrical connection (green) and f+ for nuclear connection (blue) of GenX; isosurface = 0.002 au. Fig.9c It is a parallel degradation and defluorination process.
[0084] See also Figure 9a-9c , the process of first shortening the GenX chain length in the pathway can easily occur.
[0085] In pathway I, the ether bond is first cleaved to form C 3 F 7 · and · C 3 F 4 O 3 - Then, C 3 F 7 The fragment reacts with OH- in alkaline solution to generate C 3 F 7 OH, C 3 F 7 OH is unstable and further converted into acyl fluoride (CF 3 CF 2 COF). The acyl fluoride is hydrolyzed again to form C 2 F 5 COO - (PFA), then the second C atom in PFA is attacked by the hydrated electrons, resulting in H / F exchange. Since there are abundant nucleophilic potentials around the second C atom, such as Figure 9b , PFA is further converted into CF 3 COO-(TFA). For carboxylated C 3 F 4 O 3 - Fragment, may occur -COO - The decarboxylated chain may react with water to produce unstable C 2 F 4 OOH - , the C 2 F 4 OOH - Similar to Path I, acyl fluoride can be hydrolyzed to TFA and finally decomposed to form CO 2 and F - .
[0086] In pathways II and III, the defluorination process using H / F exchange as the initial step is difficult because the degradation of GenX is more likely to start from the destruction of ether bonds or carboxyl groups. 2 O 3 The addition of e aq - The concentration and reaction efficiency of α-Fe 2 O 3 The introduction of not only enhanced the degradation and defluorination efficiency of GenX, but also broadened the degradation pathway, making the total defluorination rate reach 88.5%.
[0087] No H / F exchange was detected in the UV / S system in paths II and III. 2 O 3 The addition of aq - concentration and reaction efficiency, and greatly increased e aq - The probability of directly attacking the nucleophilic site on CF. As a result, F attached to the more nucleophilic carbon atom 6 in path III is replaced by H, which then decarboxylates and hydrolyzes to CF. 3 CF 2 CF 2 OCFOHCH 3 Because structures containing F and OH on the same carbon are usually unstable, the H of the alcohol group can easily be replaced by OH. - Extraction, then CH 3 loss, forming a non-radical intermediate CF 3 CF 2 CF 2 OCFO. Subsequently, fluoroformic acid (FCOOH) is rapidly released and decomposes into CO in an aqueous environment. 2 and HF. This reaction ultimately exposes the ether oxygen, which reacts as carbon difluoride (CF 2 O) and can be hydrolyzed to form CO 2 and two HF molecules. CF 2 CF 3 The free radicals then undergo a sophisticated “decompression” mechanism to complete mineralization.
[0088] In Pathway III, due to the inclusion of the head group, the group close to the carboxyl group may show high activity, thus providing a preferential reaction center for the first H / F exchange. 3 The loss of leads to the formation of a radical intermediate, followed by further removal of CO 2 Generate CF 3 CF 2CFH. Under the continuous attack of the hydrated electrons on the nucleophilic site of carbon atom 3, further H / F exchange occurs. Finally, CH 2 The loss of CF 2 CF 3 The formation of which undergoes a process of unwinding.
[0089] This result well confirms that the synthesized material can completely mineralize PFASs under optimal technical conditions.
[0090] Finally, it should be noted that in the present disclosure, the terms "comprises", "includes" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the presence of other identical elements in the process, method, article or device including the element.
[0091] Although the present disclosure has been disclosed above through the description of the specific embodiments of the present disclosure, it should be understood that those skilled in the art can design various modifications, improvements or equivalents to the present disclosure within the spirit and scope of the attached scheme. These modifications, improvements or equivalents should also be considered to be included in the scope of protection claimed by the present disclosure.
Claims
1. A method for preparing α-Fe2O3 material for reducing and repairing PFAS pollution in water, characterized in that: include: The precursor preparation step is as follows: dissolving a trivalent iron source to obtain an iron salt solution, adding a dispersant under stirring conditions to coat and separate the iron ions to generate a flocculent brown precipitate to obtain a precursor suspension, separating the precipitate and washing, purifying, drying, crushing and screening the precipitate in sequence to obtain a precursor; the dispersant is oleylamine, and the ratio of the amount of oleylamine added to the volume of the iron salt solution is 1:10-50; after the oleylamine is added dropwise to the stirring iron salt solution, stirring is continued at a constant speed of 300-1000r / min for 10-60min to obtain the precursor suspension; Calcination step: heat-treating the precursor in an inert atmosphere, and then crushing and sieving to obtain the α-Fe2O3 material. The target temperature of the heat treatment is 600-1000°C, and the treatment time at the target temperature is 3-12h.
2. The preparation method according to claim 1, characterized in that: In the precursor preparation step, the washing and purification treatment includes adding an appropriate amount of washing liquid to the precipitate, and washing it on an oscillator at 2500 r / min for 30 minutes, wherein the washing liquid is composed of ethanol and n-hexane in a volume ratio of 1:
4.
3. The preparation method according to claim 2, characterized in that: In the precursor preparation step, the drying process adopts vacuum freeze drying.
4. The preparation method according to claim 1, characterized in that: In the precursor preparation step, the trivalent iron source is selected from at least one of ferric nitrate, ferric nitrate nonahydrate, ferric chloride, ferric chloride hexahydrate and ferric sulfate.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The heat treatment comprises heating the precursor to 780-820° C. at a heating rate of 5±1° C. / min and then calcining at a constant temperature for 5-7 hours.
6. The preparation method according to claim 5, characterized in that: In the precursor preparation step, the screening process is to pass through a 200-mesh sieve; in the calcination step, the screening process is to pass through a 200-mesh sieve.
7. An α-Fe2O3 material for reducing and repairing PFASs pollution in water, characterized in that: The method is prepared according to any one of claims 1 to 6.
8. The α-Fe2O3 material according to claim 7, characterized in that: The α-Fe2O3 material is nanoparticles with a size of 91±27 nm, the particle size is regular and uniform, the particles are interconnected to form a layered three-dimensional structure, and the median pore diameter is 1.1285 nm.
9. An application of α-Fe2O3 material for reducing and repairing PFASs contamination in water, characterized in that: include: Using the α-Fe2O3 material as described in claim 7 or 8 as a catalyst, sulfite as a hydrated electron source material and reducing agent, and ultraviolet light as a driving light source, PFASs-contaminated water is subjected to reduction and degradation treatment.
10. The use of α-Fe2O3 material for reducing and repairing PFASs contamination in water according to claim 9, characterized in that: The ultraviolet light is a light wave emitted by a lamp source that can excite a 254nm band.
11. The use of α-Fe2O3 material for reducing and repairing PFASs contamination in water according to claim 9, characterized in that: The sulfite is at least one of sodium sulfite, sodium bisulfite, potassium sulfite and potassium bisulfite.
12. The use of α-Fe2O3 material for reducing and repairing PFASs contamination in water according to any one of claims 9 to 11, characterized in that: The application is carried out under anaerobic conditions, the dosage of the α-Fe2O3 material is 0.1-1 g / L, the dosage of the sulfite is 1-20 mmol / L, and the treatment time is 12-48 hours.
13. The use of an α-Fe2O3 material for reducing and repairing PFASs contamination in water according to claim 12, characterized in that: The anaerobic condition is a dissolved oxygen content of 0.2±0.1 mg / L.
14. The use of α-Fe2O3 material for reducing and repairing PFASs contamination in water according to any one of claims 9 to 11, characterized in that: The application is carried out under aerobic conditions, the dosage of the α-Fe2O3 material is 0.1-0.2 g / L, the dosage of the sulfite is 5-20 mmol / L, and the treatment time is 24-48 hours.
15. The use of an α-Fe2O3 material for reducing and repairing PFASs contamination in water according to claim 14, characterized in that: The aerobic condition is a dissolved oxygen content of 8.9±0.1 mg / L.